2020
DOI: 10.1016/j.elerap.2019.100901
|View full text |Cite
|
Sign up to set email alerts
|

Brands as relationship builders in the virtual world: A bibliometric analysis

Abstract: Given the growing role of brands as relationship partners and relationship facilitators and the preeminence of the online environment for consumers, this article contributes to the understanding of virtual brand-centric relationships by presenting the first bibliometric mapping analysis of the academic research into the topic from its conception until 2018. Using keyword co-occurrence, it examines 585 records and identifies the most productive countries, journals, influential authors and papers, and research c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
91
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(97 citation statements)
references
References 85 publications
3
91
0
3
Order By: Relevance
“…Given the complexity of the phenomenon, the use of multiple methods is not uncommon, especially when the behavior of people in consumption-related groups is investigated (i.e., Schau et al, 2009;Cova and White, 2010;Goulding et al, 2013). The empirical data concern consumer engagement in a digital ecosystem as captured by activities directed at brands, other consumers, and brand communities, a context that has increasingly attracted academic research interest over the last ten years (Veloutsou and Ruiz-Mafé, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the complexity of the phenomenon, the use of multiple methods is not uncommon, especially when the behavior of people in consumption-related groups is investigated (i.e., Schau et al, 2009;Cova and White, 2010;Goulding et al, 2013). The empirical data concern consumer engagement in a digital ecosystem as captured by activities directed at brands, other consumers, and brand communities, a context that has increasingly attracted academic research interest over the last ten years (Veloutsou and Ruiz-Mafé, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Reflecting current realities, recent academic scholarship has emphasized the ambient, continuous, and persistent qualities of consumer engagement (Wirtz et al, 2013) and the evolving mesh of digital technologies, which brings about seemingly endless possibilities for engagement (Akaka and Vargo, 2015;Breidbach and Brodie, 2017;Hollebeek et al, 2019;Veloutsou and Ruiz-Mafé, 2020;Venkatesan, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As in all evolving fields, the original conceptual work led first to an exploratory investigation of the phenomenon (Fournier, 1998;Ji, 2002), then its measurement (Aaker et al, 2004;Veloutsou, 2007), to a very rapid and sharp growth of the papers and the scope of the academic engagement. To date, thousands of academic articles have been published in the area (Fetscherin and Heinrich, 2015;Albert and Thomson, 2018;Fetscherin et al, 2019;Veloutsou and Ruiz-Mafé, 2020), and many concepts have been identified as, and associated to, descriptors of various forms of brand relationships (Albert and Thomson, 2018). In recent years, the concept also spanned to practitioners who developed and published measurement instruments related to brand relationships such as the Edelman's Trust Barometer [1], the Brand Index by YouGov [2], the Experience Brand Index [3] by Jack Morton, the Brand Affinity Report by Rakuten, the Brand Intimacy Study [4] by MBLM, the Loyalty Report [5] by Bond Brand Loyalty, Prophet's Brand Relevance Index [6], or the Brand Passion Report [7] by NetBase, just to mention a few.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there is no bibliometric study in the field of fitness app research, even though this type of literature has been used widely in other fields in recent years ( Zanjirchi et al, 2019 ). Bibliometrics can supplement existing experiments and review studies, help researchers identify hidden research lines, hot issues, and research methods in the field, and reduce the problems of neglecting certain excellent articles due to the deviation of researchers' subjective judgments ( Zanjirchi et al, 2019 , Veloutsou and Mafe, 2020 ).…”
Section: Introductionmentioning
confidence: 99%